Prinsip Ketatanegaraan Dalam Kisah Nabi Sulaiman As. - Agus Rizal; Hamka Hasan; Zulkifli Abdurrahman Usman (Universitas Negeri Padang, 2025)
This study aims to determine the constitutional principles contained in the Al-Quran which focuses on the story of the Prophet Sulaiman as. This research focuses on the values contained in the story of Prophet Sulaiman as. which is used as the basis or footing in the state. Methodology used was qualitative by emphasizing the library research. The emphasis on this type of research is to find various theories, laws, propositions, principles, opinions and ideas of the characters to analyze and solve the problems being studied. This study uses descriptive. The results of this study indicate that the principles of good governance are those that are based on several principles (1) Tauheidullah (2) Obedience to Leaders (3) Trust (4) Justice (5) Deliberation (6) Peace. The government system is in the form of an absolute monarchy with the source of power coming from God (theocracy), even though Prophet Sulaiman as. inherited his father's kingdom (monarchy) but he did not choose his son as the successor of leadership